2022
DOI: 10.1002/cphc.202200277
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Complete Dissociation of CO2 on Iron Clusters

Abstract: Dissociation of CO 2 on iron clusters was studied by using semilocal density functional theory and basis sets of triple-zeta quality. Fe 2 , Fe 4 , and Fe 16 clusters were selected as the representative host clusters. When searching for isomers of Fe n CO 2 , n = 2, 4 and 16 corresponding to carbon dioxide attachment to the host clusters, its reduction to O and CO, and to the complete dissociation, it was found that the total spin magnetic moments of the lowest energy states of the isomers are often quenched w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…The low-energy structures obtained for Fe 4 and Fe 16 as shown in Figure 1 agree with the low-energy clusters obtained from DFT calculations. 19 The Fe 256 cluster is also shown as an example of a larger cluster. The dimensions of the simulation boxes containing the Fe 4 and Fe 16 clusters were 25.0 × 25.0 × 25.0 Å 3 and those containing the Fe 256 cluster were 30.0 × 30.0 × 30.0 Å 3 , and they were periodic in all directions.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…The low-energy structures obtained for Fe 4 and Fe 16 as shown in Figure 1 agree with the low-energy clusters obtained from DFT calculations. 19 The Fe 256 cluster is also shown as an example of a larger cluster. The dimensions of the simulation boxes containing the Fe 4 and Fe 16 clusters were 25.0 × 25.0 × 25.0 Å 3 and those containing the Fe 256 cluster were 30.0 × 30.0 × 30.0 Å 3 , and they were periodic in all directions.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…[14][15][16][17][18] Apart from experimental investigations, there are also a considerable amount of theoretical studies focusing on transition metal-mediated reactions with CO 2 in an effort to elucidate salient features of mechanisms and kinetics. [19][20][21][22][23] Taking the electronic structure of CO 2 into consideration, the most commonly adopted method of effective activation concerns electron density donation to the antibonding π* orbital, leading to a negatively charged CO 2 moiety and further enabling overall reduction of bond strength along with bending distortion from its initial linear geometry. 2 The changes in the charge distribution and geometric structures give rise to vibrational frequency shifts regarding the asymmetric stretching mode of the CO 2 molecule.…”
Section: Introductionmentioning
confidence: 99%
“…14–18 Apart from experimental investigations, there are also a considerable amount of theoretical studies focusing on transition metal-mediated reactions with CO 2 in an effort to elucidate salient features of mechanisms and kinetics. 19–23…”
Section: Introductionmentioning
confidence: 99%
“…That study also found that both N atoms and N 2 dimers prefer cluster surface sites and do not penetrate inside the cluster. The same cluster was also recently tested as a catalyst for reactions of the CO 2 dissociation into separated atoms C and two O atoms on the surface of the cluster. Computationally, studying reactions of small molecules on small 3d-transition metal clusters makes it possible to use all-electron basis sets which can yield more precise descriptionscompared to plane wave methods that incorporate effective core potentialsof relevant electronic effects including the dependence of ground state energies on spin multiplicity which, the results of the present study show, play an important role in reaction energetics. It is now possible to synthesize size-selected subnanometer clusters of metals and metal oxides . Therefore, the catalytic activity of ultrasmall nanoparticles is now amenable to be studied in detail in the laboratory. …”
Section: Introductionmentioning
confidence: 99%
“…That study also found that both N atoms and N 2 dimers prefer cluster surface sites and do not penetrate inside the cluster. The same cluster was also recently tested as a catalyst for reactions of the CO 2 dissociation into separated atoms C and two O atoms on the surface of the cluster.…”
Section: Introductionmentioning
confidence: 99%